2018
DOI: 10.18494/sam.2018.1947
|View full text |Cite
|
Sign up to set email alerts
|

H2O2 Detection by Redox-based Potentiometric Sensors under Biological Environments

Abstract: Hydrogen peroxide (H 2 O 2) is an important target material for detecting biomolecules including acetylcholine (ACh), glutamate (Glu), and glucose. In this study, we report on H 2 O 2 detection under biological environments based on the redox reaction. The redox potential change caused by the reaction between the electron mediators of ferrocenes and H 2 O 2 catalyzed by horseradish peroxidase (HRP) was measured using a gold electrode connected to a source follower circuit. The mediators were either dissolved i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…In contrast, after the addition of H 2 O 2 at approximately 60 s, ∆V Out for 1 µM H 2 O 2 and more significantly became larger than that for the control. Note that the temporal drop of V Out at the H 2 O 2 addition is an artifact [47]. Although its origin should be investigated, the difference in ∆V Out was observed among the H 2 O 2 concentration.…”
Section: H 2 O 2 Sensing Characteristicsmentioning
confidence: 91%
See 1 more Smart Citation
“…In contrast, after the addition of H 2 O 2 at approximately 60 s, ∆V Out for 1 µM H 2 O 2 and more significantly became larger than that for the control. Note that the temporal drop of V Out at the H 2 O 2 addition is an artifact [47]. Although its origin should be investigated, the difference in ∆V Out was observed among the H 2 O 2 concentration.…”
Section: H 2 O 2 Sensing Characteristicsmentioning
confidence: 91%
“…In a recent development, the sensor array with 256 × 256 pixels shrunk its pixel area down to 2 µm with the temporal resolution of 0.5 ms [45], showing the potential as a high spatio-temporal pH imaging technique. It was also demonstrated that the array applies to the detection of biomolecules including ACh [46] and ATP [47,48], based on acid generation by an enzymatic reaction. Although the CTT sensors showed the potential for the imaging of NTs, they suffer from low output signals in the application to living organisms including cells and tissues [48].…”
Section: Introductionmentioning
confidence: 99%
“…(A) Potentiometric probes measure the 162 potential between a working and reference electrode in a system with no significant current flow [18-23].163 (B) Amperometric sensors use two or three electrodes and measure the change in current while the Parrilla et al created a potentiometric H2O2 sensor in 2017 by coating platinum electrodes withthat the Nafion coating decreased signal interference from ascorbate, which commonly interferes membrane containing glucose oxidase was used to detect blood glucose levels[58]. The sensor is a low-In 2018, Iwata et al used a previously-reported glutamate sensor, which was based on the redox 181 reaction of a gold electrode[59], as an H2O2 sensor that functioned independently of the pH of the 182 solution[60]. Iwata et al showed that both a ferrocenyl methanol solution and a 11-ferrocenyl-1-183 undecanethiol-coated electrode were capable of H2O2 detection but that the ferrocenyl methanol 184 solution had a lower detection limit[60].…”
mentioning
confidence: 99%
“…The sensor is a low-In 2018, Iwata et al used a previously-reported glutamate sensor, which was based on the redox 181 reaction of a gold electrode[59], as an H2O2 sensor that functioned independently of the pH of the 182 solution[60]. Iwata et al showed that both a ferrocenyl methanol solution and a 11-ferrocenyl-1-183 undecanethiol-coated electrode were capable of H2O2 detection but that the ferrocenyl methanol 184 solution had a lower detection limit[60].…”
mentioning
confidence: 99%